REMEDIASI MISKONSEPSI SISWA PADA MATERI SUHU DAN KALOR MENGGUNAKAN STRATEGI PREDICT-OBSERVE-EXPLAIN - Fendy Firmanto; Tomo Djudin; Syaiful B. Arsyid (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThis research aims to determine the effectiveness of the predict-observe-explain (POE) strategy assisted by learning videos in reducing student’s misconceptions on temperature and heat material in SMA Kemala Bhayangkari Kubu Raya. The form of research used was pre-experimental design with one group pre-test post-test design. Data collection tool in the form of 9 multiple choice questions with 3 alternative answers accompanied by open reasons. The sample of this research is the students of class XII MIA 1 consisting of 29 people selected as a sample saturated with intact group techniques. The results of the test reliability test of 0.84 (very high category). Decrease in average misconceptions per student by 44%. Through the McNemar test, there was a conceptual change in students with a significance test obtained by average ????ℎ???????????????????? 2 (10.33)> ???????????????????????? 2 (3.84) for the value of α = 5%, db = 1. From the results of the calculation of Cohens’s effect size obtained d = 0.31. (low category). A predict-observe-explain (POE) strategy assisted by learning videos is expected to be used as an alternative to remediation activities in overcoming misconceptions experienced by students.Keywords: misconceptions, predict-observe-explain, remediation, temperature and heat, video learning